2016
DOI: 10.1177/0267658316657134
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and conceptual factors in Spanish–English bilinguals’ processing of lexical categories in their two languages

Abstract: This study examines possible semantic interaction in fully fluent adult simultaneous and early L2 bilinguals. Monolingual and bilingual speakers of Spanish and English (N=144) were tested for their understanding of lexical categories that differed in their two languages. Simultaneous bilinguals came from homes in which Spanish or Spanish and English were spoken when they were children, and L2 bilinguals entered the US as children. Accuracy data show higher ultimate attainment of languagespecific semantic knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…watch, whereas English wall encompasses Spanish pared and muro. Gathercole et al (2016) argued that when lexical items have a broad category in one language it is relatively harder to distinguish more precise categorisation in another language. Moreover, Gathercole et al (2016) acknowledged that restructuring relates to conceptual underpinning.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…watch, whereas English wall encompasses Spanish pared and muro. Gathercole et al (2016) argued that when lexical items have a broad category in one language it is relatively harder to distinguish more precise categorisation in another language. Moreover, Gathercole et al (2016) acknowledged that restructuring relates to conceptual underpinning.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Gathercole et al (2016) argued that when lexical items have a broad category in one language it is relatively harder to distinguish more precise categorisation in another language. Moreover, Gathercole et al (2016) acknowledged that restructuring relates to conceptual underpinning. They showed that (L2) polysemous lexical items such as leg are conceptually plausible and accordingly easier to restructure in the L2 than homophones.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Other findings suggest that bilinguals tend to adopt the use of broader semantic categories over more specific ones in lexical areas where their languages differ in semantic granularity, at least for some semantic categories (cf. Gathercole, Stadthagen-González, Pérez-Tattam, & Yavas, 2017). Klɛŋ is a fine example of both these tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data have not always supported this prediction, however. For instance, Jessen and Cadierno (2013) found learners trying to create distinctions in L2 to match those in their L1 (see also Gathercole & Moawad, 2010; Gathercole, Stadhagen-Conzalez, Perez-Tattam, & Yavas 2017; Jarvis, 2000).…”
Section: Introductionmentioning
confidence: 99%